Prevalence and characteristics of e-cigarette users in Great Britain: Findings from a general population survey of smokers - Brown, Jamie (Elsevier Science, 2014)
BACKGROUND: E-cigarettes may be effective smoking cessation aids and their use by smokers has been growing rapidly. It is important to observe and assess natural patterns in the use of e-cigarettes whilst experimental data accumulates. This paper reports the prevalence of e-cigarette awareness, beliefs and usage, including brand choice, and characterises the socio-demographic and smoking profile associated with current use, among the general population of smokers and recent ex-smokers. METHODS: Data were obtained from 3538 current and 579 recent ex-smokers in a cross-sectional online survey of a national sample of smokers in Great Britain in November and December 2012. Differences between current and recent ex-smokers in the prevalence of e-cigarette awareness, beliefs and usage were examined and the socio-demographic and smoking profile associated with current use of e-cigarettes was assessed in a series of simple and multiple logistic regressions. RESULTS: Ninety-three percent of current and recent ex-smokers (n = 3841) were aware of e-cigarettes. Approximately a fifth (n = 884) were currently using e-cigarettes, whilst just over a third (n = 1507) had ever used them. Sixty-seven percent of the sample (n = 2758) believed e-cigarettes to be less harmful than cigarettes; however, almost a quarter (n = 994) remained unsure. Among both current and recent ex-smokers, the most popular reasons for using were health, cutting down and quitting (each > 80%) and 38% used the brand ‘E-lites’. Among current smokers who were aware of but had never used e-cigarettes, approximately half (n = 1040) were interested in using them in the future. Among current smokers, their use was associated with higher socio-economic status (OR = 1.48, 95%CI = 1.25–1.75), smoking more cigarettes (OR = 1.02, 95%CI = 1.01–1.03) and having a past-year quit attempt (OR = 2.82, 95%CI = 2.38–3.34). CONCLUSIONS: There is a near universal awareness of e-cigarettes and their use appears to be common among smokers in Great Britain although a quarter of all smokers are unsure as to whether e-cigarettes are less harmful than cigarettes. E-lites – a brand that delivers a low dose of nicotine – is the most popular. E-cigarette users appear to have higher socio-economic status, to smoke more cigarettes per day and to have attempted to quit in the past year.